Praktik Kesalehan Pemuda pada Kota Provincial: Studi pada Majelis At Tho’at - Rizkidarajat, Wiman; Mutahir, Arizal; Hanny P, Isna; Putri M, Aulia; Romauli , Nethania (Kamaya: Jurnal Ilmu Agama, 2024)
Since the New Order collapsed in 1998, Islamization in Indonesia has become a mainstream movement. Evidence of mainstreaming Islamization is the increasingly common practice of piety in public spaces. One of the most common Islamization efforts is efforts to purify Islam through hijrah movement carried out by youth groups through popular culture media, such as through music in metropolitan cities in Indonesia such as Jakarta, Bandung and Yogyakarta. The hijrah movement is often carried out by targeting young people who have experienced transgressive life practices, causing the exploitation of space. This research aims to portray the practice of piety that occurs in provincial cities or second-class cities in the city dichotomy, according to Van Klinken. The research method used in this research is descriptive qualitative with a case study approach. Ethnographic data collection was carried out for six months, from November 2023 to May 2024, with the primary data source being a youth study collective in Purwokerto called Majlis At Tho'at. The findings of this research are that the At Tho'at Assembly's pious practices are carried out by creating two types of space that came from youth creativity in term to redefined hijrah movement. The first is a private room in the form of exclusive recitations, which are held regularly in the residence of one of the assembly members. The second is public space in the form of piety exhibitions in public spaces through a band, which is formed through social interaction in private spaces through recitations. The research results show that piety in provincial cities does not always exist in a binary dichotomy, which results in the exploitation of space as occurs in metropolitan cities. This is proven by the existence of spaces to negotiate a social phenomenon that occurs in a city.